Disputes on the issues of insurance of ships with participation as a party a legal entity of a foreign state: from the practice of Russian courts. Issue 4 (2nd October 2019) - Turitsyn, Dmitry
ABSTRACT: In the article researched the law-enforcement practice of the Russian courts of Arbitration jurisdiction. The author analyses the current regulatory acts governing the marine insurance, as well as judicial decisions and resolutions of Russian courts on insurance claims payable due to the payment of losses as a result of the destruction of ship with the participation of foreign individuals and legal entities. The author concludes that judges often side with policyholders. Thus, compliance with the norms of the Russian trade and procedural law allows foreign persons to protect their assets, as well as to receive decent protection of its rights in Russian courts.